Unicuspid aortic valve concomitant with aortic insufficiency presenting with infectious endocarditis: a case report - Naoko Yuzawa-Tsukada; Toshikazu D. Tanaka; Satoshi Morimoto; Michihiro Yoshimura (Journal of Medical Case Reports, 2019)
Abstract Background A unicuspid aortic valve is a rare congenital cardiac abnormality. Despite its uncommon finding on an initial presentation, aortic insufficiency is accompanied with unicuspid aortic valve and this might reflect the natural history of progression in the morphology of unicuspid aortic valve. Case presentation We describe a 65-year-old Japanese man who was evaluated for endocarditis and found to have a unicuspid aortic valve concomitant with moderate aortic insufficiency, which was, owing to the lack of evidence of valve membrane destruction, independent of underlying infectious endocarditis. In addition, aortic insufficiency was progressed because of nonbacterial thrombotic endocarditis on the ventricular side, in areas of high turbulence around the heart valve. Conclusions Our case is unusual given the unicuspid aortic valve concomitant with aortic insufficiency, which was presumably independent of underlying infectious endocarditis because of the location of the vegetation and the lack of evidence of valve destruction. Therefore, attention should be paid to a variety of complications in the setting of unicuspid aortic valve.